Normalization of Aperiodic Electrocorticography Components Indicates Fine Motor Recovery After Sensory Cortical Stroke in Mice. Issue 9 (30th June 2022) - Biskamp, Jonatan; Isla Cainzos, Sara; Higgen, Focko L.; Gerloff, Christian; Magnus, Tim
Abstract : Background: Electrophysiological signatures of ischemic stroke might help to develop a deeper understanding of the mechanisms of recovery. However, to identify critical windows for novel treatment approaches, suitable readout parameters in vivo with the potential to close the gap between functional modifications within the peri-infarct cortex and behavioral outcome on the systems-level are still lacking. Methods: Wild-type mice were trained in a skilled reaching task and underwent permanent distal medial cerebral artery occlusion or sham intervention. Functional deficits and their recovery were monitored both behaviorally and electrophysiologically recording multichannel electrocorticography from both hemispheres. Results: Ischemic strokes are located in sensory cortical areas. Affected mice presented fine motor deficits of their contralateral forepaw. Analyses of electrocorticography signals from awake animals demonstrated a modulation of the shape of power spectral density in the vicinity of the infarct. While power spectral density consists of both rhythmic oscillatory and nonrhythmic, aperiodic components, the alteration of spectrum shape was reflected in a transient increase of aperiodic exponents in the peri-infarct cortex. The relative power and frequency of slow oscillations remained unchanged. Exponents derived from motor areas significantly correlated with fine motor recovery, thus indicating functional modifications of neuronal activity. Conclusions: Aperiodic spectral exponents exhibited a unique spatiotemporal profile in the mouse cortex after stroke and might complement future translational studies providing a dynamic link from pathophysiology to behavior.